Analysis and Design of Accounting Information System on CV Indo Sangkar Emas - Meissy Lengmas Congdinata; Alexandra Adriani Widjaja; Ridwan Sanjaya (Soegijapranata Catholic University, 2022)
Using an Accounting Information System in a company can help the company in enhancing its performance. CV Indo Sangkar Emas is facing some problems at their business, such as frequently finding duplicate data, giving code to its data, recording purchase and sales transactions, and making financial statement all done manually. All the problems caused by the company still not using an Accounting Information System. Therefore, the company decided that they need Accounting Information System. The research aims to analyze and design Accounting Information System that can improve data accuracy, Quality Control, and financial statement quality on CV Indo Sangkar Emas, and improve communication between warehouse employees and office employees. The System will be developed using the Object-Oriented Analysis and Design method with the help of observation, interview, documentation, and Unified Modeling Language, such as use case diagram and class diagram.